Effects of chemical modification and nanotechnology on wood properties - Bi Wenzhai; Li Haitao; Hui David; Gaff Milan; Lorenzo Rodolfo; Corbi Ileana; Corbi Ottavia; Ashraf Mahmud (Nanotechnology Reviews, 2021)
As a green material, wood is widely used in building decoration, railway construction, and other fields. However, the wood itself has inherent defects of being easy to absorb water and deform, rot, and decrease in strength. The physical and mechanical strengths and stability of artificial fast-growing forest wood are even worse. As wood modification can improve the dimensional stability, durability, strength, and other properties of wood, it has been widely used. Chemical modification is the main method of wood modification. The development of nanotechnology has brought more possibilities for wood modification. Owing to the extensive literature available, this article summarizes the representative achievements of wood chemical modification and nanotechnology. The principle, production process, advantages, and disadvantages of various wood chemical modification methods were analyzed, compared, and evaluated. Finally, according to the application status of wood-modified materials, the problems existing in the current wood chemical modification methods and the application of nanotechnology, and the development trend in the future are analyzed.